A Unique Cause of Intestinal and Splenic Infarction in a Sickle Cell Trait Patient. (7th May 2013) - Asfaw, Sofya H.; Falk, Gavin A.; Morris-Stiff, Gareth; Tuthill, Ralph J.; Moorman, Matthew L.; Samotowka, Michael A.
Abstract : Sickle-cell trait is a common genetic abnormality in the African American population. A sickle-cell crisis in a patient with sickle-cell trait is uncommon at best. Abdominal painful crises are typical of patients with sickle cell anemia. The treatment for an abdominal painful crisis is usually medical and rarely surgical. We present the case of a cocaine-induced sickle-cell crisis in a sickle-cell trait patient that resulted in splenic, intestinal, and cerebral infarctions and multisystem organ failure necessitating a splenectomy, subtotal colectomy, and small bowel resection. This case highlights the diagnostic dilemma that abdominal pain can present in the sickle-cell population and illustrates the importance of recognizing the potential for traditionally medically managed illnesses to become surgical emergencies.